A dynamic homogenization model for long-wavelength wave propagation in corrugated sandwich plates. (December 2018) - Lou, Jia; Yang, Jie; Kitipornchai, Sritawat; Wu, Huaping
Highlights: A dynamic homogenization model is developed for corrugated sandwich plates. Analytical solutions are derived for low-frequency dispersion relations. The spectral element method is used to validate the homogenization model. Abstract: In the present work, a new dynamic homogenization model is developed to investigate the long-wavelength wave propagation in a corrugated sandwich plate. With the harmonic motion assumption and using a shifting operator, the governing equations of the plate are firstly represented in a state-space form. Then, a dynamic homogenization model is developed via the two-scale homogenization method. Based on this model and considering the propagation of sinusoidal waves, the dispersion relations and corresponding wave modes can be easily obtained. In order to validate the developed homogenization model, the obtained dispersion relations are compared with those predicted by the spectral element method. It is found that the present method gives accurate results in low frequency range. Furthermore, the effects of some geometric and material parameters on the dispersion relations for the corrugated sandwich plate are also discussed. The developed homogenization model is expected to be helpful in the prediction and control of dynamic responses of corrugated or even lattice sandwich structures. Graphicalabstract : Image, graphical abstract